Challenging Cocacolisation of Rural Nepali Market: The Role of Education - Dhungana, Raj Kumar; Pfefferle, Alexandra (Journal of Education and Research, 2016)
The shelves of local shops are filled with an abundance of imported beverages. Coca-Cola, Pepsi, Fanta, Sprite, Frooti, and Red Bull among others have made the way to rural Nepal, where agriculture is still the primary source of income. As the result of increasing access to imported goods and products in rural markets, local products are gradually losing ground. This paper shows that tailored consumer education can assist de-cocacolising the market and increase the competitiveness and diversification of local products. It does so by imparting knowledge and skills to individuals to be critical and responsible consumers who start seeking an equal share of local products in the rural market. For this paper, extensive desk review, rural market observations and interviews with consumers of different age groups, vendors and youth were used as data generation techniques.